Tail, Tusk, and Trunk: What Different Metrics Reveal About Racial Disproportionality in School Discipline. Issue 1 (2nd January 2019) - Girvan, Erik J.; McIntosh, Kent; Smolkowski, Keith
Abstract : There are substantial racial disparities in school discipline but little agreement on how best to measure them. The choice of metric can influence conclusions about the magnitude of racial discipline disproportionality and intervention effectiveness. This article describes 2 common (risk ratio, risk difference) and 3 relatively novel (standardized effect size, raw differential representation, discipline rate) approaches to evaluating racial disproportionality, with illustrations of their strengths and weaknesses. Its concludes with a discussion of the metrics and a recommendation that researchers and policymakers consider the raw number of students of color differentially disciplined, as among the easiest to understand, the most stable, and capturing the widest range of information. Even so, no metric captures all relevant aspects of disproportionality. Accordingly, researchers and policymakers should be deliberate in their specific aims in measuring discipline disproportionality and select a combination of metrics that provides information most responsive to their goals.